2005
DOI: 10.1016/j.jtcvs.2005.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Who would be a candidate for bridge to recovery during prolonged mechanical left ventricular support in idiopathic dilated cardiomyopathy?

Abstract: Patients with severe congestive heart failure caused by dilated cardiomyopathy have a good chance of myocardial recovery and successful explantation of the left ventricular assist system. A relatively slow response of myocardial recovery during prolonged left ventricular assist system support was demonstrated in some patients. A lesser degree of fibrotic changes in the left ventricle was predictive of recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 22 publications
1
48
1
Order By: Relevance
“…[42][43][44] Patients with a broad scar lesion, which is assessed by end-myocardial biopsy, cardiac magnetic resonance imaging, or myocardial scintigraphy, have less chance to achieve LVRR. 45,46) Simon, et al showed that a short duration of HF is a positive factor to achieve LVRR during LVAD treatment, because remodeling is not severe in such myocardium and there is a chance to recover. 47) We have demonstrated that preoperative "insufficient" β-blocker treatment is a strong predictor of LVRR during LVAD treatment.…”
Section: Preoperative β-Blocker Treatment and LV Reverse Remodeling (mentioning
confidence: 99%
“…[42][43][44] Patients with a broad scar lesion, which is assessed by end-myocardial biopsy, cardiac magnetic resonance imaging, or myocardial scintigraphy, have less chance to achieve LVRR. 45,46) Simon, et al showed that a short duration of HF is a positive factor to achieve LVRR during LVAD treatment, because remodeling is not severe in such myocardium and there is a chance to recover. 47) We have demonstrated that preoperative "insufficient" β-blocker treatment is a strong predictor of LVRR during LVAD treatment.…”
Section: Preoperative β-Blocker Treatment and LV Reverse Remodeling (mentioning
confidence: 99%
“…Type 1 collagen, type 1: type 3 collagen ratio, collagen cross linking and fibrosis have been shown to be elevated in a variety of clinical as well as experimental disease states (Avendano et al 1999;Badenhorst et al 2003;Marijianowski et al 1995;Mukherjee and Sen 1991;Porter and Turner 2009;Woodiwiss et al 2001). Reports of LVAD-induced ECM changes have been conflicting, with some revealing increased myocardial fibrosis and ECM volume following unloading (Klotz, S. et al 2005b;Li et al 2001;Matsumiya et al 2005;Saito et al 2010), and others showing a reduction (Akgul et al 2004;Bruckner et al 2001;Maybaum et al 2007;Thohan et al 2005;Thompson et al 2005). Bruggink et al demonstrated a biphasic response with initial expansion of ECM and then a subsequent regression with prolonged MU (Bruggink et al 2006).…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) are a group of enzymes responsible for collagen degradation and are tightly regulated by tissue inhibitors of metalloproteinases (TIMPs). HF is associated with large changes in MMP and TIMP action and thus ECM composition (Li et al 2001;Matsumiya et al 2005), and it is understood that altered regulation in their expression contributes to "negative" ECM remodelling in HF (Mann and Spinale 1998;Spinale et al 2000;Wilson and Spinale 2001). Normalisation (decrease) of MMP1:TIMP1 ratio has been reported with LVAD use in a DCM population and coincides with increased LV collagen cross linking, type 1: type 3 ratio and increased ventricular stiffness (Klotz,S et al 2005b).…”
Section: Extracellular Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…5 However, there are only limited data about the long-term results of LVR in Japan. Furthermore, because of a specific situation related to the severely limited supply of organ donors and the limited availability of cardiac support devices, such as the ventricular assist system, 6 we have adopted liberal inclusion criteria for LVR, even for critically ill patients who are generally treated with mechanical circulatory support and subsequent heart transplantation. 7 Consequently, it is meaningful to examine our own experiences of LVR.…”
mentioning
confidence: 99%